(untitled) (Doctor Virtualis, 2024)
The paper focuses on a central juncture in the long crisis that touches Eucharistic doctrine in the Middle Ages, namely the alleged dispute between Paschasius Radbertus and Ratramnus of Corbie in the ninth century regarding the presence of Christ in the sacrament: in figure or in truth? Starting from the observation that the visions of the two monks are not opposed, as was believed from the 10th-11th centuries onward, we intend first to show that theirs are complementary attempts to translate within clear and unambiguous categories the vagueness of patristic doctrine. In order to explain the origin of this need for clarification, we show how the Corbian context was permeated by the influence of the first return of Aristotelianism (the logica vetus) on the basis of a broader Carolingian program of modernization of society and rationalization of doctrine. The Eucharistic crisis, the first signs of which can be seen in Corbie, thus appears as a bargaining over the meaning of patristic doctrine in order to preserve a balance between symbolism and realism, made necessary as the effect of a logical-ontological paradigm shift in order to preserve the unity of the faith and thus of the Christian community. This crisis will close only with the doctrine of transubstantiation, at the end of a long process of rationalization taken over by a class of experts of theology.